2014
DOI: 10.1002/app.41638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short fiber tip geometry and inhomogeneous interphase on the stress distribution of rubber matrix sealing composites

Abstract: The normal and interfacial shear stress distributions with flat fiber tip of short-fiber-reinforced rubber matrix sealing composites (SFRC) compared with the shear lag model were investigated by using the finite element method (FEM). The results indicate that stress values do not agree with those calculated by the shear lag model. The effect of different geometrical shapes of fiber tip on the stress distributions of SFRC was also investigated. The geometrical shapes of fiber tip under present investigation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Thus, our numerical results do not contradict Eshelby’s solution. In fact, they are consistent with results from computational models of short fiber reinforced composites4546, full-field elasticity solutions for rigid line inclusions47, and photoelasticity experiments on line-like inclusions48. Based on the insight gained from our computational mechanics calculations, we modeled the effect of the spongin by replacing the tractions applied to the ends of the RoC with opposing point forces, ± P M at the Sxa’s ends (see Fig.…”
Section: Resultssupporting
confidence: 79%
“…Thus, our numerical results do not contradict Eshelby’s solution. In fact, they are consistent with results from computational models of short fiber reinforced composites4546, full-field elasticity solutions for rigid line inclusions47, and photoelasticity experiments on line-like inclusions48. Based on the insight gained from our computational mechanics calculations, we modeled the effect of the spongin by replacing the tractions applied to the ends of the RoC with opposing point forces, ± P M at the Sxa’s ends (see Fig.…”
Section: Resultssupporting
confidence: 79%
“…However, inconsistencies are still exist. For example, thin interface thickness and high interface Young's modulus resulted in efficient stress transfer at the fiber interface using a simple representative volume element (RVE) approach based on the finite element analysis (FEA) [2], while results simulated by Yu et al [3] indicated that the normal stress increased with the increase of the interface thickness and interfacial shear strength (IFSS) remained unchanged, and the interface modulus had no influence on the stress distributions along the direction to the fiber axis. Kim and Mai [4] also reported that there were inconsistencies on the influence of thickness and modulus on the LTE.…”
Section: Introductionmentioning
confidence: 98%
“…ε 0 is the axial tensile strain at r = r m . The aspect ratio of fiber s can be written as f / slr = (9) When the shear stress at the interface reaches a critical value τ a , the friction sliding will happen. Ordinarily, the frictional resistance is less than τ a .…”
Section: Shear-lag Modelmentioning
confidence: 99%
“…A number of micromechanics models have been developed to predict the stress transfer, among which the shear-lag model [6,7] and the finite element analysis [8,9] are the most widely used. Yuan et al [10] presented an interphase layer mode to describe the interphase of composites and analyzed the effects of the interphase thickness and interfacial shear strength on the peak load.…”
Section: Introductionmentioning
confidence: 99%